Human biology of poverty - Varela-Silva, M. I.; Santinho, C. (Annals of Human Biology, 2016)
Poverty has its nefarious roots embedded in social, political, and economic disadvantages and inequalities (Psaki et al., Citation2012; Leatherman, Citation2005). It differentially affects various segments of populations, intensifies negative outcomes of growth and development, creates ill-health in terms of infectious and non-communicable diseases, and furthers discrimination in all spheres of life (Bogin et al., Citation2014; Delisle, Citation2008; Leatherman, Citation2005; Nandy et al., Citation2015). The complex effects of poverty on individuals and societies vary throughout the lifespan. These outcomes are more often seen among ethnic minorities, migrants, and women and girls (Goudet et al., Citation2011; Mocumbi & Sliwa, Citation2012; Smith et al., Citation2002; Teixeira, Citation2008). Poverty also strikes differently between developed and developing countries (Amuna & Zotor, Citation2008; Bogin et al., Citation2014; Smith et al., Citation2006; Varela-Silva et al., Citation2012). In extreme situations, such as war and other catastrophes, people are forcefully displaced. These refugees are disproportionately affected if they already live in poverty (Clarkin, Citation2012; Devakumar et al., Citation2014).